Analisis kinerja keuangan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia dengan menggunakan Metode Multi Attribute Decision Making (MADM) - Lalonsang, Junior T. A.; Karamoy, Herman (Yayasan Widyantara Nawasena Raharja, 2024)
Financial performance analysis is an essential tool for objectively evaluating the health and effectiveness of banks. This study aims to analyze the financial performance of banking companies listed on the Indonesia Stock Exchange using the Multi Attribute Decision Making (MADM) method. This research is qualitative with a descriptive and comparative approach. The Analytic Hierarchy Process (AHP) method is used to determine the criteria weights, while the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is employed to rank the companies based on their performance. The data used includes key financial ratios such as DER, ROA, ROE, NIM, Cost to Income Ratio, Operating Margin, Current Ratio, and Quick Ratio. The results show that based on the AHP method, Bank Tabungan Pensiunan Nasional Syariah (BTPS) has the best performance, followed by Bank Central Asia (BBCA), Bank Rakyat Indonesia (BBRI), Bank Mega (MEGA), and Bank Mandiri (BMRI). Meanwhile, the TOPSIS method results indicate that Bank Tabungan Pensiunan Nasional Syariah (BTPS) remains in the top position, followed by Bank Central Asia (BBCA), Bank Mega (MEGA), Bank Rakyat Indonesia (BBRI), and Bank Mandiri (BMRI). These differences highlight the variation in the relative assessment of each criterion depending on the approach used. This study concludes that MADM, particularly AHP and TOPSIS, is effective in comprehensively and objectively evaluating the financial performance of banking companies, providing valuable insights for stakeholders in the Indonesian banking sector.